Indonesian Tax Reform: Inappropriate Policy Choices or Administrative Problems - Bambang Irawan (Indonesian Association for Public Administration (IAPA), 2019)
Purpose -Tax reform in Indonesia has entered a new phase known as the third chapter of reform. This reform has been established out since 2017 and has a target until 2024. The current reform is the biggest in history because it involves changes in the five main pillars, namely organizations, Human Resources, Information Technology and Databases, Business Processes, and Tax Regulations. The purpose of the article is to explore how taxation can accelerate representative democracy and how the tax institution can strengthen the capacity of the government in tax collection. Design/methodology/approach-This article uses a conceptual approach that is rooted in the tax reform, administration, and tax policy literature. Findings - The contribution of this article is twofold. First, it provides a concept of tax reform to accelerate representative democracy by tax administration and policy. Second, this paper examines the policy choices of tax institutions to strengthen the capacity of the government in tax collection. Practical implications - This article helps tax institutions, researchers, and policymakers better understand the implications of tax reform by using appropriate policy choice and tax administration implemented by tax institutions.